O instituto da translatio iudicci no código de processo civil brasileiro (CPC 2015) : as nulidades como invalidades no direito processual - Vale, Daniel Felipe Ramos (2022)
The present research focuses on procedural nullity, especially the institute of translatio iudicii, analyzing it as a consistent amendment of the 2015 CPC that allows the use of procedural acts and, therefore, acts as an appropriate instrument for the consolidation of substantive law. It presents the theme of nullity from an analysis in comparative law on a general theory of procedural nullity, and then goes on to explain its materialization in the Brazilian Civil Procedural Code (CPC) of 2015. It is a bibliographic research, based on the deductive method, which carries out a review of the literature on the subject, the nullity in the Civil Procedural Code, in particular the translatio iudicii. The bibliographic research made the survey of several articles from the databases of Scielo, Vlex and Revista dos Tribunais. At the same time, a survey was carried out on the jurisprudence on the subject from the search tool on the website of the STJ (Superior Court of Justice) and other state courts. Finally, it was understood that this form of nullity is well described in the current Brazilian procedural code, but there are situations shown below, in the position of judges, who become more formalistic and nullity can become a tool for obstruction of substantive law. The research did not intend to exhaust the subject studied, contributing with legal operators to a deeper analysis between the relationship between procedural law and substantive law. It is understood that, as a result of the research, the excess of formalism in the application of nullity without considering how the 2015 CPC has been presenting the issue of translatio iudicii proves to be an obstacle in the pursuit of the core material law.